2012
DOI: 10.1002/jbm.a.34426
|View full text |Cite
|
Sign up to set email alerts
|

Phase composition control of calcium phosphate nanoparticles for tunable drug delivery kinetics and treatment of osteomyelitis. I. Preparation and drug release

Abstract: Developed in this study is a multifunctional material for simultaneous osseoinduction and drug delivery, potentially applicable in the treatment of osteomyelitis. It is composed of agglomerates of nanoparticles of calcium phosphate (CAP) with different monophasic contents. The drug loading capacity and the release kinetics were investigated on two model drug compounds with different chemical structures, sizes and adsorption propensities: bovine serum albumin and fluorescein. Loading of CAP powders with small m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2
1

Relationship

5
5

Authors

Journals

citations
Cited by 82 publications
(62 citation statements)
references
References 47 publications
(51 reference statements)
1
58
1
Order By: Relevance
“…However, it is well-known that bacteria can be adsorbed and replicated on the TCP surface [5], inducing serious implant-related infections. One way of coping with this issue is to administer antibiotics postoperatively, either systemically or locally, the latter of which is thanks to the ability of calcium phosphate cements to bind antibiotics and release them sustainably [6]. The use of antibiotics is, however, costly and is linked with the global problem of rising immunity of pathogens to traditional antibiotic therapies [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is well-known that bacteria can be adsorbed and replicated on the TCP surface [5], inducing serious implant-related infections. One way of coping with this issue is to administer antibiotics postoperatively, either systemically or locally, the latter of which is thanks to the ability of calcium phosphate cements to bind antibiotics and release them sustainably [6]. The use of antibiotics is, however, costly and is linked with the global problem of rising immunity of pathogens to traditional antibiotic therapies [7].…”
Section: Introductionmentioning
confidence: 99%
“…The more rapid body fluid flow, reducing the concentration of dissolution units in the near vicinity of the implant, while simultaneously buffering it at a fairly constant level elsewhere, is another factor that greatly affects the resorption rate and is not so readily mimicked under in vitro conditions. Coupled to attrition to mimic cyclic mechanical loading, frequent solvent replenishments indeed promoted dissolution of DCP in buffered saline, perhaps by interfering with the protective HAP layer formation at physiological pH [42]. These results have implicitly suggested that different chemical environments and different mechanical loads greatly affect the degradation profile of CP implants and reiterated the unusual complexity of their fate in the body.…”
Section: Introductionmentioning
confidence: 99%
“…This surface layer of the drug bound by weak forces to the particle predisposes HAp to exhibit burst release and prevents it from being used as a sustained release platform in the dispersed form. Powder compaction and drug capturing within the pores is an approach that overcomes this deficiency of HAp 13,14,15,16 , but limits the use of such composites to application as solid blocks. Although entrapment of fluorophores has been reported for glassy, silicate calcium phosphates prepared in an amorphous form in Igepal-based reverse micelles and stabilized with citric acid 11 , the compound naturally present in bone where it coats HAp crystals at 0.5 molecules/nm 2 and prevents their coalescence in the collagen matrix 11 , it appears that loading HAp with organics in any amount greater than that present in nacre or tooth enamel (< 3 wt%) via intercalation is not possible.…”
Section: Peculiarities Of Hapmentioning
confidence: 99%